Implementasi Teknologi Digital untuk Penyusunan Laporan Keuangan dan Media Promosi pada UMKM Gula Aren - Jenni Veronika Br Ginting; Eka Feby Ronauli Lubis; Fikaria Br Tarigan (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
The sugar palm MSME (UMKM gula aren) as a partner has significant potential to grow, but it still faces challenges in financial record-keeping and promotional strategies. Its financial records are maintained manually and in a simple format, while product marketing is still limited to local networks without utilizing digital technology. These conditions hinder improvements in productivity, transparency, and the competitiveness of sugar palm products. Through this program, the implementation team provided education on preparing simple financial reports, promotional strategies through social media and online marketplaces, practical training on product packaging to increase product value, as well as technological equipment to support the partner’s production process. The partner actively participated, both in learning how to prepare financial reports and in using social media for product promotion. The results of the activities showed an improvement in the partner’s ability to maintain clearer, more transparent, and more structured financial records, make use of digital media (Instagram and Shopee) to expand marketing reach, and develop product innovations through more attractive and competitive packaging designs. The initial impact of this program includes increased confidence among MSME actors in managing their business and the expansion of marketing networks for sugar palm products. In the future, this program is expected to contribute to improving the local community’s welfare, strengthening the MSME’s position in the supply chain, and providing a digital-based empowerment model for other small businesses.